Three days in January [large type] : Dwight Eisenhower's final mission - Baier, Bret; Whitney, Catherine (HarperLuxe an imprint of HarperCollinsPublishers, 2017)
Analyzes the last three days of the presidency of Dwight D. Eisenhower in January, 1961, including their foundations in Eisenhower's personal experiences as well as their effects on the presidency of John F. Kennedy and beyond.